2019
DOI: 10.1088/1755-1315/381/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anthropogenic activities on the temperature regime of soils of the South-Western Baikal region

Abstract: Soil temperature is a key factor controlling many biotic and abiotic processes in soils. Monitoring of the soil temperature in the different habitats is an urgent task, as a rare meteorological network does not allow to assess in detail the hydrothermal regime of different territories. The territory of the study is the Tunka intermountain basin – the area of discontinuous distribution of permafrost. The atmospheric-soil measuring complex was used to investigate the hydrothermal regime of soils. Observations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…Kukkonen et al (2020) found that the permafrost thawed most rapidly in low-porosity soils, whereas high-porosity soils in the top layer (e.g., peatland) will retard thawing considerably. Similarly, the depth of a seasonally frozen layer and the temperature regime of peat soils in the oligotrophic bog in the southern taiga zone of Western Siberia showed significant differences at sites with high and low levels of bog waters (Kiselev et al, 2019). Both Kukkonen et al (2020) and Kiselev et al (2019) results are in line with previous conclusions on the importance of volumetric water content and unfrozen water content for soil thermal properties governing heat transfer and phase change processes (Romanovsky and Osterkamp, 2000).…”
Section: New Methodologies Determining Earth Surface Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…Kukkonen et al (2020) found that the permafrost thawed most rapidly in low-porosity soils, whereas high-porosity soils in the top layer (e.g., peatland) will retard thawing considerably. Similarly, the depth of a seasonally frozen layer and the temperature regime of peat soils in the oligotrophic bog in the southern taiga zone of Western Siberia showed significant differences at sites with high and low levels of bog waters (Kiselev et al, 2019). Both Kukkonen et al (2020) and Kiselev et al (2019) results are in line with previous conclusions on the importance of volumetric water content and unfrozen water content for soil thermal properties governing heat transfer and phase change processes (Romanovsky and Osterkamp, 2000).…”
Section: New Methodologies Determining Earth Surface Characteristicssupporting
confidence: 88%
“…Similarly, the depth of a seasonally frozen layer and the temperature regime of peat soils in the oligotrophic bog in the southern taiga zone of Western Siberia showed significant differences at sites with high and low levels of bog waters (Kiselev et al, 2019). Both Kukkonen et al (2020) and Kiselev et al (2019) results are in line with previous conclusions on the importance of volumetric water content and unfrozen water content for soil thermal properties governing heat transfer and phase change processes (Romanovsky and Osterkamp, 2000). Locally, the sites with thin snow cover (e.g., hill tops) demonstrated higher resistance to the thawing (Williams and Smith, 1989;Kukkonen et al, 2020).…”
Section: New Methodologies Determining Earth Surface Characteristicssupporting
confidence: 88%
“…Similarly, the depth of a seasonally frozen layer and the temperature regime of peat soils in the oligotrophic bog in the southern taiga zone of West Siberia showed significant differences between the sites with high and low levels of bog waters (Kiselev et al, 2019). Both Kukkonen et al (2020) and Kiselev et al (2019) results are in line with previous conclusions on the importance of volumetric water content and unfrozen water content for soil thermal properties governing heat transfer and phase change processes (Romanovsky and Osterkamp, 2000). Locally, the sites with a thin snow cover (e.g.…”
Section: New Methodologies Determining Earth Surface Characteristicsmentioning
confidence: 96%
“…Issues related to the causes, scales and consequences of the wildfire impact on the landscapes receive a high attention in the literature (Akharzhanova, 2004;Elaev et al, 2013;Lazareva & Afonina, 2014;Ivanyo et al, 2017;Kiselev et al, 2019;Maksyutova et al, 2019). In these sources, fluctuation features of the long-term wildfire activity are revealed; factors of their occurrence are indicated; ecosystem characteristics at fire-damaged areas are presented at the initial stage of regeneration.…”
Section: Introductionmentioning
confidence: 99%